Exposure of Developing Male Rats to One or Multiple Noise Sessions and Different Housing Conditions: Hippocampal Thioredoxin Changes and Behavioral Alterations - Molina, Sonia Jazmín (2022)
The perinatal temporal window is a highly vulnerable time in which environmental factors, such as nutrients, drugs, infections, chemicals, and stress, experienced by the mother can be communicated to the offspring and produce lasting consequences on the new-born brain, thus contributing the evolutionary origin of non-communicable neuropsychiatric diseases. Most of these disorders are preventable, since they are due to modifiable risk factors such as lifestyle and the environment.Nevertheless, the increase in perinatal exposure to drugs, substances of abuse, pathogens, nutritional deficits and in immune over-reactivity can partly explain the high prevalence of neuropsychiatric disorders over recent decades. They include teratogenesis, dysfunction of the reproductive, neurocognitive and immune systems, autism, and addiction, all of which may have a substantial economic and societal impact. Similarly, adolescence is truly a dynamic and unique period of one´s life. Adolescence is often considered to begin around the onset of puberty and culminate with the acquisition of adult social roles, although considerable inter-individual variability exists in these rough demarcations. During this time span, considerable change occurs across multiple domains (e.g., physical, cognitive, socio-emotional). Since adaptations to novelty and environmental challenges are prerequisites that make teenagers the most fully crucially adaptive human beings around, the relationship between exposure to environmental factors of vulnerability and onset of neuropsychiatric disturbances needs to be addressed.It is, therefore, necessary to take stock of the latest evidence regarding the underlying molecular mechanisms of epigenetics leading to vulnerability - or resilience - to neuropsychiatric diseases. On this basis, some of the major experts in the field will contribute to this Research Topic in order to share the most recent findings in the field.Covering the topic will have worldwide implications to orient the research towards the dimly addressed epigenetic mechanisms that underlie the perinatal origins of neuropsychiatric diseases and will help healthcare professionals towards a broader awareness, effective prevention and successful therapeutic strategies.